The relationship of the use of mask with the event of acute respiratory tract infection (ARI) in Rice Miller workers in Peukan Bada District, Aceh Besar - Nasrullah; Sofia; Kartini (Science Midwifery, 2022)
Acute Respiratory Infection (ARI) has become a serious problem for rice mill workers. the majority of workers working in rice mills have inhaled dust from rice grains produced by milling and drying. Use PPE masks during the rice milling process is an alternative to reduce the incidence of ARI. Therefore, the purpose of this study was to determine the relationship between the use of masks and the incidence of ARI among rice mill workers in Peukan Bada District, Aceh Besar. This research is descriptive analytic with a cross-sectional design. This research was conducted in July at the Rice Mill, Peukan Bada District, Aceh Besar. The population in this study were workers in the rice mill as many as 25 workers from 5 rice mills in Peukan Bada District, Aceh Besar. The sample in this study is the total of the population. The results of the study show that there is a relationship between the availability of PPE with the incidence of ARI among rice mill workers in Peukan Bada District, Aceh Besar with a p value of 0.012. there is a relationship between the method of use and the incidence of ARI among rice mill workers in Peukan Bada District, Aceh Besar with a p value of 0.001. Mask suitability has no relationship with the incidence of ARI among rice mill workers in Peukan Bada District, Aceh Besar with a p value of 0.43.